PENANAMAN NILAI-NILAI KARAKTER MELALUI MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN PADA SISWA KELAS VII DI MTS AL- KHAIRIYAH TEGALINGGAH - Moh. Febriyandy; I Wayan Landrawan; Sukadi Sukadi (Program Studi PPKn Jurusan Hukum dan Kewarganegaraan Undiksha Singaraja, 2021)
This study aims to determine 1) the process of inculcating character values through Civics subjects in grade VII A MTs Al-Khairiyah Tegalinggah, 2) Obstacles in inculcating character values through Civics subjects, and 3) Efforts made to overcome these barriers. The purpose of this study was to describe the process of inculcating character values through Civics subjects in class VII A MTs Al-Khairiyah Tegalinggah. The location of this research is in class VII A of MTs Al-khairiyah Tegalinggah. Data collection methods used in this study were observation, interviews, and documentation. The data analysis method used is descriptive qualitative with the following steps: data reduction, data presentation, and conclusion drawing or verification. The results showed that 1) the process of inculcating character values through Civics subjects went quite well using the following approaches: Cultivating values by example, strengthening fanism. Like the teacher always comes on time, speaks well, and is neatly dressed, occasionally gives praise, and gives reprimands; The cognitive moral approach is carried out by conducting group discussions on moral dilemmas, such as discussing ways to express opinions freely and responsibly; Value clarification approach by means of simulation such as simulating deliberation; Approach to learning to do (action) by way of appeal and habituation.